Penerapan Model Pembelajaran Cooperative Learning Teknik Jigsaw Untuk Meningkatkan Kerjasama Peserta Didik Dalam Menyelesaikan Tugas Mata Pelajaran IPAS Secara Kelompok Pada Peserta Didik Kelas V SD Negeri 01 Ngadirejo, Kartosuro, Tahun Pelajaran 2023/202 - Erna Erlia; Muhroji Muhroji; Ana Zumratus Saadah (Departement of Mathematics Education, 2024)
This classroom action research aims to prove that the application of the Cooperative Learning Jigsaw Technique learning model can increase student cooperation in completing science subject assignments in groups for class V students at SD Negeri 01 Ngadirejo. Classroom Action Research procedures are carried out through a flow process consisting of 4 stages, namely: 1) planning; 2) implementation; 3) Observation; and 4) reflection. From the data analysis it is known that in each cycle there is an increase in the completeness of student learning outcomes. The learning outcomes of the initial study students only reached 40% with an average score of 59.9, in the first cycle learning outcomes increased to 54% with an average score of 70.18, but this increase was not as expected in the research performance indicators. The application of the Cooperative Learning Jigsaw Technique learning model in cycle II has increased student learning outcomes from 54% in cycle I to 100% of students completing learning with an average score of 81.45 in cycle II. Based on the results of this research data analysis, it can be concluded that the application of the Cooperative Learning Jigsaw Technique learning model can increase student cooperation in completing science subject assignments in groups for class V students at SD Negeri 01 Ngadirejo, Kartosuro.